2,4-Thiazolidinediones as PTP 1B Inhibitors: A Mini Review (2012-2018) - Verma, Sant K.; Yadav, Yatesh Sharad; Thareja, Suresh (Mini Reviews in Medicinal Chemistry, 2019)
2,4-thiazolidinedione (TZD) scaffold is a synthetic versatile scaffold explored by medicinal chemists for the discovery of novel molecules for the target-specific approach to treat or manage number of deadly ailments. PTP 1B is the negative regulator of insulin signaling cascade, and its diminished activity results in abolishment of insulin resistance associated with T2DM. The present review focused on the seven years journey (2012-2018) of TZDs as PTP 1B inhibitors with the insight into the amendments in the structural framework of TZD scaffold in order to optimize/design potential PTP 1B inhibitors. We have investigated the synthesized molecules based on TZD scaffold with potential activity profile against PTP 1B. Based on the SAR studies, the combined essential pharmacophoric features of selective and potent TZDs have been mapped and presented herewith for further design and synthesis of novel inhibitors of PTP 1B. Compound 46 bearing TZD scaffold with N-methyl benzoic acid and 5-(3-methoxy-4-phenethoxy) benzylidene exhibited the most potent activity (IC50 1.1 μM). Imidazolidine-2,4-dione, isosteric analogue of TZD, substituted with 1-(2,4-dichlorobenzyl)-5-(3-(2,4- dichlorobenzyloxy)benzylidene) (Compound 15) also endowed with very good PTP inhibitory activity profile (IC50 0.57 μM). It is noteworthy that Z-configuration is essential in structural framework around the double bond of arylidene for the designing of bi-dentate ligands with optimum activity.
Keywords: Imidazolidinedione